Evaluasi Persentase Karkas Ayam Kampung Super Dengan Pemberian Jermai Jagung Fermentasi - Frangki Sigaha; Ellen J Saleh; Srisukmawati Zainudin (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2019)
This study aims to determine the evaluation of the percentage of super native chicken carcasses by providing fermented corn straw. The research design used in the study was a Completely Randomized Design consisting of 5 treatments and 4 replications namely P0 (ration without treatment), P1 (ration containing 5% fermented corn straw), P2 (ration containing 10% fermented corn straw), P3 (ration ration containing 15% fermented corn straw) and P4 (ration containing 20% fermented corn straw). The data obtained were then analyzed using the Analysis of variance (ANOVA) and if the results were influential then proceed with the Duncan Distance test. The results showed that the treatment had no significant effect (P> 0.05) on the variables of life weight, carcass weight and percentage of carcass cut. The highest living weight was found in the P0 treatment (without using fermented corn straw) with the acquisition of an average value of 850.75 gr / head and produced the highest carcass weight of 197.25 gr. The highest percentage of carcass cuts was obtained at P3 treatment (15% fermented corn straw) with an average value of 23.88%.